Challenges of Rural Teachers' Development in Remote Areas of Western China - Zhongzhuoma, Yong; Abdul Aziz, Nor Azni (Journal of Public Administration and Governance, 2023)
This paper discusses the challenges of rural teachers' development in Western China. Rural teachers are the backbone of China's basic education as well as the key and future of rural basic education development. How to inject and retain rural teachers as well as stabilize the ranks of rural teachers is fundamental to improving the quality of rural basic education, including promoting rural revitalization. Via the investigation of rural schools in Western China, this paper discovered that there are still several challenges in the development of rural teachers, for instance, teacher structure deviation, low overall educational background, serious substitute teachers, few training times, simple training methods, poor training effect, and serious teacher loss. According to the interview results, the existing challenges among rural teachers are analyzed, and recommendations are given, which include obtaining a rational allocation of teacher resources, optimizing the teacher structure, strengthening teacher training, enhancing the overall quality of teachers, and improving the incentive system in detail.